PELAYANAN FRONTLINER PADA PT. IVAN WISATA NUSANTARA DI KOTA PEKANBARU - ', Safitri; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Frontliner PT. Ivan Wisata Nusantara Pekanbaru strives to provide optimal service for customer comfort. Namely by making a departure schedule on time, providing documents regarding information during the trip to customers, responding well to special customer requests, being responsible and helping with customer problems, helping with travel documents, as well as dealing with every customer complaint and problem. Frontliner Service at PT. Ivan Wisata Nusantara in Pekanbaru City. Receiving Guests, Serving Customers, Selling Products, Building Good Relations and Contacting Customers. This research uses a qualitative method with a qualitative descriptive approach to describe and explain the situation that occurred by collecting data and information in the field. The key informants in this research are the Main Director, Employees and Customers. In this research, the data collection techniques used were interviews, observation and documentation. Based on the research results, it can be concluded that having a uniform is mandatory, providing a comfortable waiting room, prioritizing service, providing service in good language, providing solutions and providing good facilities for customers. Kata Kunci : Services, Frontliner, Travel Agency